Tools of Neuroscience - Raff-Biggemann, U; Fredes-Donoso, P (Springer International Publishing, 2020)
This chapter intends to name and describe briefly the most important groups of techniques used in neuroscience. Two groups of techniques are discussed in more detail: electrophysiologic and imaging methods for being particularly important in neuroscience and for being of special interest for psychologists. Ideally, the reader should be informed about the potential and the shortcomings of the diverse methods, from the physical background to economic considerations. A special effort has been made to describe and explain the modern imaging techniques, particularly magnetic resonance imaging, for being of outstanding importance in cognitive neuroscience and, hence, in psychology. © Springer Nature Switzerland AG 2021.
Keywords: Connectomics; EEG; fMRI; Nuclear medicine; Optogenetics; Patch clamp; Recording techniques; Transcranial stimulation